DINAMIKA PERDAGANGAN DAN ADAPTASI STRATEGIS: RESPON KOREA SELATAN TERHADAP PEMBATASAN IMPOR SEMIKONDUKTOR JEPANG, 2019-2021 - Putri, Nafisyah Viona; Yunita, Primadiana (DAS Institute, 2023)
The semiconductor sector, pivotal in the global value chain, sees countries like South Korea carving specializations. Notably, South Korea leads in semiconductor memory but relies heavily on Japanese imports, causing significant trade deficits. This dependency became problematic when historical tensions spurred Japan's export restrictions to South Korea, threatening the semiconductor supply chain and bilateral relations. Addressing this between 2019-2021, South Korea invoked Friedrich List's productive power theory, strategizing via infant industry nurturing and forced capital infusion. They launched the K-Semiconductor Strategy, promoting domestic growth to counterbalance import reliance. This proactive stance attracted 510 trillion KRW in investments, including private, foreign, and government subsidies, bolstering the local semiconductor materials sector. The outcome was twofold: reduced import dependence and a demonstration of South Korea's productive power, affirming its capability to sustain and fortify its semiconductor stronghold despite geopolitical strains. This period underscored the criticality of self-reliant industrial advancement in the face of international dynamics and supply vulnerabilities.